The Relationship Of Entrepreneur Behavior In The Implementation Of Hygien Sanitation With Food Management In The Home Industry - Nurdin, Ambia; Zakiyuddin, Zakiyuddin; Astini, Dewi; Mulyadi, Mulyadi; Mahyuddin, Mahyuddin; Megawati, Cut; Usman, Bukhari; Bahri, Idal (Aceh Sanitation Journal, 2024)
In Indonesia, there have been 115 extraordinary events (KLB) due to food poisoning. In addition, it is also known that food poisoning in Indonesia is caused by processed food products at home by 40.87% and processed food products by 24.35%. Home industry food in West Aceh as many as 48 businesses while in Johan Pahlawan District there are 40 businesses. This study aims to determine the relationship between entrepreneur behavior in implementing Hygiene sanitation with food management in home industries in Johan Pahlawan District, West Aceh Regency. This study is descriptive analytical with a Cross Sectional design, with a population of 40 with a sample in this study being 40 home industry entrepreneurs in Johan Pahlawan District. The sampling technique in this study used the Total Sampling method. Based on the results of the study, it shows that the independent variables (attitudes and actions) have a relationship with food management where Pvalue <α (0.05) while Knowledge has no relationship where Pvalue> α (0.05). To the relevant agencies to further improve counseling, supervision and monitoring of the Home Industry households and to the Home Industry household entrepreneurs to further increase their awareness of the importance of managing food properly.